117 Incidental finding of coronary artery calcification in non-triggered high-resolution thoracic computed tomography: a retrospective study of reporting standards in a single trust. (5th June 2017) - Saluja, Sushant; Pavel, Janousek; Raj, Divya; Irwin, Bruce; Zhu, David; Gray, Timothy; Hargreaves, Mark; Sett, Aung; Anderson, Simon
Abstract : Aims: Coronary artery calcium (CAC) score is an important tool in determining the risk of developing heart disease. The measurement of this score has traditionally been based on using ECG triggered computed tomography (CT). Emerging evidence has revealed that there is excellent concordance between gated and non-gated CT scans in identifying CAC. We aimed to evaluate the incidental prevalence and burden of CAC on non-gated High Resolution CT (HRCT) thorax used for patients undergoing lung cancer screening or follow-up for interstitial lung disease. Methods: Computerised Radiology Information Service (CRIS) was manually searched to determine all HRCT scans performed in our Trust from 01/05/2015 to 01/05/2016. The reports issued by Radiologists and images of selected studies were reviewed. Results: 2152 HRCT scans were performed over this period. Patients were divided into three groups of age <50 (Group 1); 50-<60 (Group 2) and 60 (Group 3). 100 scans were randomly selected from each group using a random number generator to give a total of 300 patients. The mean ages of patients in Group 1, 2 and 3 were 42.7±2.3, 57.4±1.4 and 66±2.7 respectively. There was, approximately, the same number of males as females in each group. CAC was seen in 10% of scans in Group 1, 85% of scans in Group 2% and 92% in Group 3. CAC was only reported in 2/10 (20%) of scans in?Group 1, 39/85 (45.9%) in Group 2 and 41/92 (44.6%) in Group 3. No scan commented on the absence of calcification. For the positive reports Agatston scores were not calculated and CAC was perceptually graded a mild, moderate or severe. SS and PJ independently calculated the Agatston scores of HRCT scans whose reports did not comment on the degree of calcification (105/187). We excluded 15/105 (14.3%) scans as they were uninterpretable due to motion artefacts. Of the remaining 90 scans analysed 63/90 (70%) had severe CAC with an Agatston score of >400 with the remaining showing moderate calcification (101–400). Cohen Î° agreement between the two authors rating was 0.88 (95% confidence interval [CI] 0.82–0.94). Group 2 and 3 had significantly more patients with severe CAC then group 1 (p<0.001). Left anterior descending artery was most commonly affected. Conclusion: This study shows that CAC is under reported on non-gated HRCT scans. Given that respiratory disease is an independent risk factor for developing cardiac disease, we believe that CAC must be reported on patients having imaging for respiratory conditions. By mentioning the degree of CAC as a standard when reporting non-gated HRCT scans, we can risk-stratify patients and refer them to cardiologists for further investigations, such as stress-echo and commence them on medications for primary prevention of cardiovascular disease. The images of calcified coronary arteries may also potentially have a role in convincing people to make correct lifestyle choices.